Harmonisasi Perlindungan Harta Kekayaan Anak dalam Perwalian melalui Penguatan Peran Wali Pengawas - Pratiwi, Yulita Dwi (Jurnal Suara Hukum, 2019)
Guardianship is the supervision of children who are no longer under the authority of their parents, and the management of objects or property of the children carried out by the guardian. In carrying out their duties, the guardian is supervised by the guardian supervisor, which based on Article 366 Indonesian Civil Code, the authority is given to the Weskamer. This office is one of the technical implementation units under the Ministry of Law and Human Rights. However, the supervision process can hardly be carried out by the Weskamer, that relates to its role that requires synergy with the role of other institutions. It shows that there is disharmony in the implementation of protection of children's assets in guardianship, which eliminates the element of supervision by the state through the Weskamer. Therefore, an idea is needed in harmonizing the protection of children's assets in guardianship through strengthening the role of guardian. This research uses normative method which is a part of legal research. Normative legal research aims to find solutions to juridical problems that arise from legal issues and provide prescriptions on these legal issues. Based on the results of the study, systematic and concrete steps are needed to improve the rules by harmonizing laws as well as institutions regarding the protection of the assets of the children by strengthening the role of guardian supervisor.Â Â